Uji Validasi dan Kepraktisan Lembar Kerja Mahasiswa Berbasis Keterampilan Proses Sains - Dian Samitra; Harmoko Harmoko (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to test the validation and practicality of student worksheets (LKM) based on the science process skills of dragonflies in the invertebrate zoology course. The method used is Research and Development 4D model. The developed worksheets were tested for feasibility (validation) to material, media and language experts, and practicality tests to students. The results showed that the feasibility test (validation) of material experts, the LKM developed, had 81.17%. The validation results of media experts got a score of 89.60%; from linguists, it was 88.57%. The results of the practicality test for students earned a score of 80.51%. In conclusion, the student worksheet validation test results based on the science process skills of dragonflies in the invertebrate zoology course are very valid. The practicality test results for students are in the practical category. Keywords: Practicality, Process Skills, Worksheet, Validation